Improved Production of Xylanase in Pichia pastoris and Its Application in Xylose Production From Xylan - Miao, Ting; Basit, Abdul; Liu, Junquan; Zheng, Fengzhen; Rahim, Kashif; Lou, Huiqiang; Jiang, Wei (Frontiers in Bioengineering and Biotechnology, 2021)
Xylanases with high specific activity has been focused with great interest as a useful enzyme in biomass utilization. The production of recombinant GH11 xylanase (MYCTH_56237) from Myceliophthora thermophila has been improved through N-terminal signal peptide engineering in P. pastoris. The production of newly recombinant xylanase (termed Mtxyn11C) was improved from 442.53 to 490.7 U/mL, through a replacement of α-factor signal peptide with the native xylanase signal peptide segment (MVSVKAVLLLGAAGTTLA) in P. pastoris. Scaling up of Mtxyn11C production in a 7.5 L fermentor was improved to the maximal production rate of 2503 U/mL. In this study, the degradation efficiency of Mtxyn11C was further examined. Analysis of the hydrolytic mode of action towards the birchwood xylan (BWX) revealed that Mtxyn11C was clearly more effective than commercial xylanase and degrades xylan into xylooligosaccharides (xylobiose, xylotriose, xylotetraose). More importantly, Mtxyn11C in combination with a single multifunctional xylanolytic enzyme, improved the hydrolysis of BWX into single xylose by 40%. Altogether, this study provided strategies for improved production of xylanase together with rapid conversion of xylose from BWX, which provides sustainable, cost-effective and environmental friendly approaches to produce xylose/XOSs for biomass energy or biofuels production.